Toy packing box - JIANWU LU (2005)
The utility model relates to a paper board packing box, in particular to a paper board packing box used for packing toy. The packing box comprises a rectangular box body 1, and the front side and the back side of the box body are provided with a sealing tongue 2. The box surface is provided with a view window 3, a transparent baffle 4 is arranged on the view window, and the box surface is provided with a box surface cover 5. The box surface cover is hinged by the extension of the connecting body of the side wall plates of the box body, and magnetic attracting fasteners 6, 7 are arranged at the fastening tongue 8 of the box surface cover and the corresponding position of the side wall. The utility model has the advantages of novel structure, convenient operation, beautiful appearance, etc. The added value of the toy is improved.